Gender, Space and Place : The Experience of Servants in Rural Households 1550-1750 - Flather, Amanda (2017)
Este artículo examina la organización y el uso del espacio doméstico de los sirvientes durante el siglo XVII y en hogares de clase media. Relaciona los modelos de cambio arquitectónico y social con las formas en que los individuos describieron su experiencia y uso del espacio doméstico en los registros judiciales. Concluye que, si bien existía una tendencia a separar el trabajo y los espacios de vida de los sirvientes del resto de la familia, una casa moderna temprana no era aquella en la que los patrones sociales rígidos y estáticos estaban mapeados. Una serie de factores sociales lucharon por definir el carácter social de un espacio, una lucha que giró en torno a los conceptos de control y uso en lugar de separación o segregación según el estatus o el género. Los patrones espaciales fueron efímeros, no obstante, es posible ilustrar cómo algunos aspectos de las relaciones sociales de la familia se reflejaron y se reforzaron por la forma en que se organizó y utilizó el espacio doméstico.
This article examines the organisation and use of domestic space by servants for eating and sleeping, looking particularly at the seventeenth century and at middling sort households, broadly defined. It relates models of architectural and social change to the ways that individuals described their experience and use of domestic space in court records. It concludes that while there was a trend to separate the work and living spaces of servants from the rest of the family, an early modern house was not one where rigid and static social patterns were mapped upon its spaces. A number of social factors struggled to define the social character of a space, a struggle which largely pivoted around the concepts of control and use rather than separation or segregation according to status or gender. Spatial patterns were ephemeral. Nonetheless, it is possible to illustrate how some aspects of the social relations of the household were reflected in and reinforced by the way that domestic space was organised and used. Moreover, the implications of such use and organisation carry important messages about the nature of the household itself
Keywords: Casa; Espacio; Servicio doméstico; Género; Sirvientes; Siglo XVII; House; Space; Servants; Gender